https://doi.org/10.36873/agp.v20: PENGARUH DOLOMIT DAN KOTORAN AYAM TERHADAP PERUBAHAN BEBERAPA SIFAT KIMA TANAH SULFAT MASAM DAN PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) The Effect of dolomite and chicken manure to some soil chemical properties of acid sulfate soil and growth of maize cr, Basuki1) and Sitompul, T. J. 2) - Admin journal (Fakultas Pertanian Universitas Palangka Raya, 2019)
ABSTRACTThis research was conducted in the Analitic laboratory of Palangka Raya Univercity and in the screenhouse of Agriculture Cultivation Department, Palangka Raya Univercity. The purpose of thisexperiment was to determine the effect of dolomit and chicken manure to some soil chemicalproperties of acid sulfate soil and growth of Maize Crop (Zea mays L.). The research was arranged inComplete Ramdomized Design with two factors and three replications. The first factors were level ofdolomit with three levels namely 0 ; 1,5 ; 3,0 times exchangeable alumunium. The second factors werelevel of chicken manure with three levels namely 0, 6 and 12 t ha-1. The results showed that theinteraction between dolomit and chicken manure significantly affected increasing the soil pH anddecreasing exchangeable alumunium. The combination level of dolomit in level 1,5 timesexchangeable alumunium with application of 6 ton.ha-1 chicken manure will be optimum increasingthe soil pH and decreasing exchangeable alumunium. The application a single factor of dolomit notsignificantly affected P-availabilityand growth of Zea mays (plant height, number of leaf and area leafindex) in age 2, 3, 4, 5, 6 weeks after planting. The application of chicken manure only significantlyaffected increasing P- availabilityand growth of Zea mays (plant height, number of leaf and area leafindex) in age 2, 3, 4, 5, 6 weeks after planting. Optimum dosage of chicken manure was 6 t ha-1.Keywords: sulfate soil, dolomite, soil chemical, chicken manures.